Nano-extract of Acalypha hispida Increased Cu,Zn-SOD Antioxidant in Pancreas of Diabetic Rat - Siti Sa'diah; Hamzah Alfarisi; Tutik Wresdiyati; Berry Juliandi (Indonesian Journal of Pharmaceutical Science and Technology, 2023)
Nanotechnology has rapidly grown in various research fields to treat oxidative stress in diabetes,including medicine and phytomedicine. Previous research showed that Acalypha hispida has strongantioxidant activity in vitro and anti-hyperglycemic activity in vivo. However, the size reductionin the crude extract should be applied to decrease the doses and increase the efficacy. The researchobjective was to evaluate the nano-extract of A. hispida leaves on Cu,Zn-SOD antioxidant content inthe pancreas of diabetic rats. The analysis of Cu,Zn-SOD antioxidant content was carried out usingimmunohistochemistry. Cu,Zn-SOD content of pancreas in diabetic rats (DMC) was significantlylower than in normal rats (NLC). The antioxidant content of Cu,Zn-SOD in MET, CAH, NAH3, andNAH6 groups was significantly higher than in the DMC group of the pancreas of diabetic rats. Nanoextractof A. hispida showed a better effect in increasing Cu,Zn-SOD antioxidant content than crudeextract. The result concluded that nano-extract of A. hispida leaves increased Cu,Zn-SOD antioxidantcontent in the pancreas of diabetic rats.